Carfilzomib, Pomalidomide, and Dexamethasone As Second-line Therapy for Lenalidomide-refractory Multiple Myeloma - Sonneveld, Pieter; Zweegman, Sonja; Cavo, Michele; Nasserinejad, Kazem; Broijl, Annemiek; Troia, Rosella; Pour, Ludek; Croockewit, Sandra; Corradini, Paolo; Patriarca, Francesca; Wu, Kalung; Droogendijk, Jolanda; et al. (HemaSphere, 2022)
This phase 2 trial investigated reinduction with carfilzomib, pomalidomide, and dexamethasone (KPd) and continuous pomalidomide/dexamethasone in patients at first progression during lenalidomide maintenance. The second objective was to evaluate high-dose melphalan with autologous stem cell transplantation (HDM/ASCT) at first progression. Patients were eligible who had progressive disease according to International Myeloma Working Group (IMWG) criteria. Treatment consisted of 8 cycles carfilzomib (20/36 mg/m2), pomalidomide (4 mg) and dexamethasone. Patients without prior transplant received HDM/ASCT. Pomalidomide 4 mg w/o dexamethasone was given until progression. One hundred twelve patients were registered of whom 86 (77%) completed 8 cycles of KPd. Thirty-five (85%) eligible patients received HDM/ASCT. The median time to discontinuation of pomalidomide w/o dexamethasone was 17 months. Best response was 37% ≥ complete response, 75% ≥ very good partial response, 92% ≥ partial response, respectively. At a follow-up of 40 months median PFS was 26 and 32 months for patients who received KPd plus HDM/ASCT and 17 months for patients on KPd (hazard ratio [HR] 0.61, 95% confidence interval [CI] 0.37-1.00, P = 0.051). PFS was better after longer duration of prior lenalidomide (HR 3.56, 95% CI 1.42-8.96, P = 0.035). Median overall survival (OS) was 67 months. KPd-emerging grade 3 and 4 adverse events included hematologic (41%), cardiovascular (6%), respiratory (3%), infections (17%), and neuropathy (2%). KPd followed by continuous pomalidomide is an effective and safe triple drug regimen in second-line for patients previously exposed to bortezomib and/or refractory to lenalidomide.